DISTRIBUSI DAN PREFERENSI HABITAT UDANG AIR TAWAR CARIDINA ENSIFERA SCHENKEL, 1902 PADA DUA INLET DANAU POSO, SULAWESI TENGAH - Setiawati, Ni Luh; Annawaty, Annawaty (Univ. Tadulako, 2019)
The distribution and habitat preference of freshwater shrimps Caridina ensifera Schenkel, 1902 on two inlets of Lake Poso, Central Sulawesi have been studied. Freshwater shrimps samples was collected in two streams, namely the Pomua Palandu Stream and Toinasa Stream. The sampling station on each streams is divided into three locations based on the distance of the stream flow from its mouth at Lake Poso. Sampling is done by purposive sampling method using the tray net tool. The obtained samples were preserved using 96% alcohol and than identification was carried out at the Laboratory of Animal Biosystematic and evolution, Department of Biology, Tadulako University. The results showed that Caridina ensifera was only distributed in the lower reaches of the Pomua Palandu Stream and Toinasa Stream, having habitat preferences between plant roots that dangled into the water with rocky sand and sand substrates and very slow current speeds. According to von Rintelen and Cai (2009) Caridina ensifera is distributed in Lake Poso.